FACTORS AFFECTING ONLINE SHOPPING PREFERENCE AMONG UNIVERSITI UTARA MALAYSIA (UUM) STUDENTS - Rushanim Hashim; Tay Yee Vern (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Purchasing products online has been a new way of life since electronic devices were introduced to society. This phenomenon is increasing in Malaysia as youngsters prefer to purchase things online rather than purchase them in-store. This study is conducted to examine the level of online shopping preference and investigate the relationship between security, saving time, and payment methods with online shopping preference among UUM students. This study used a quantitative approach with 200 students from UUM. The data was collected by using Google Forms with a five-point Likert Scale. Other than that, this study uses Statistical Package for the Social Sciences (SPSS) in analyzing the data by conducting Reliability Test, Validity Test, Descriptive Statistics Analysis, Spearman Correlation Analysis, and Regression Analysis. Based on the findings, the security level of online shopping platforms has a positive and significant impact on online shopping preferences among UUM students.